Perkembangan Tata Rias Wajah Dan Tata Busana Pada Tahun 2015-2019 Dalam Acara Jember Fashion Carnaval(JFC) Di Jember - Puteri, Diana Agustia; Suhartiningsih, Suhartiningsih (Universitas Negeri Surabaya, 2021)
Jember Fashion Carnival (JFC) was first founded by Dynan Fariz as the owner of a fashion house in Jember which was first held in 2001 in the city of Jember. Make-up and fashion are very important components in this carnival, where the development of reaching 2019 is not easy, the development of this JFC must undergo a better change from the previous year, to maintain the big carnival that has become the culture of the people of Jember. The development of make-up and fashion in the implementation of the Jember Fashion Carnaval (JFC) which took place in Jember was one of the backgrounds for the formation of this article, knowing the development of JFC implementation in 2015-2019 was the main purpose of this article, especially developments in the field of make-up and makeup. Fashion every year. The type of research method in this scientific work is a qualitative descriptive research method, which explains the development of make-up and clothing in the implementation of JFC. This research was conducted by conducting interviews with one of the JFC participants, one of the JFC designers, and one of the people in charge of JFC implementation. The purpose of this article is to explain and discuss developments in make-up and fashion in the implementation of JFC in 2015-2019. The result of the research is that in the field of make-up and fashion, this JFC event has developed very well, with different themes and concepts that are applied differently each year, this carnival undergoes a modification process to become more feasible to appear, so that JFC is transformed into an event worthy of competing with. another city. Keywords: Development of make-up and clothing Jember Fashion Carnaval (JFC) 2015-2019